Energy Management System using Evolutionary Mating Algorithms for Optimizing Energy Usage and User Comfort in Office Building - Alvin, Bob; Husnayain, Faiz; Sudiarto, Budi; Setiabudy, Rudy (Universitas Indonesia, 2024)
Indonesia has set a target to reduce emissions by 29% or 835 million tons of CO2 by 2030, which was increased to 32% or 912 million tons of CO2 in 2023. The building sector is one of the largest contributors to emissions in Indonesia. To reduce these emissions, the Indonesian government has issued energy conservation regulations requiring each sector to reduce energy consumption. According to Government Regulation No. 33 of 2023, energy conservation is mandatory for energy users in the building sector who use energy sources equivalent to or greater than 500 Tons of Oil Equivalent. One way to conserve energy is by implementing energy-efficient technologies, without compromising the comfort of building users, which includes thermal and visual comfort as part of indoor environmental quality (IEQ). An energy-efficient technology using the Evolution Mating Algorithm (EMA) is proposed. This study will discuss energy use without compromising building user comfort in tropical countries using the EMA optimization algorithm. The study demonstrates that EMA successfully optimizes energy use without reducing user comfort in tropical countries.